Improvement of immune cell functions in aged mice treated for five weeks with soybean isoflavones. - Baeza Monedero, Isabel; Castro de Frutos, Nuria María de; Alvarado, Carmen; Alvarez Lazaro, Pedro; Arranz, Lorena; Bayon, Julian; de la Fuente, Mónica (My University, 2005)
El envejecimiento se asocia a un deterioro del sistema inmunitario y a un descenso de diversas hormonas, como los estrógenos. Los fitoestrógenos de la dieta se han propuesto como alternativa a la terapia hormonal sustitutiva, y se considera que los efectos beneficiosos de la soja se deben principalmente a sus isoflavonas, cuyo papel inmunomodulador suscita creciente interés. El objetivo de este trabajo fue analizar si la administración durante cinco semanas de una dieta enriquecida en isoflavonas de soja y té verde podía modificar la función inmune de ratones sometidos a cirugía simulada u ovariectomía. Se evaluó la actividad de células NK y la linfoproliferación frente a concanavalina A y lipopolisacárido en leucocitos peritoneales. Ambos tratamientos mejoraron de forma notable estos parámetros frente a los controles, sugiriendo que las isoflavonas podrían ayudar a atenuar los efectos del envejecimiento mediante la mejora de funciones inmunes clave.

Aging is associated with an impaired immune system as well as with a decline of several hormones, such as estrogens. Dietary phytoestrogens have been proposed as an alternative to hormone replacement therapy. The beneficial action of soybean compounds is probably due to isoflavones, whose role as immunomodulators has been investigated with increasing interest. The aim of the present work was to study whether a 5-week administration of a diet enriched in soybean isoflavones and green tea could influence the immune function of mice that were sham-operated or ovariectomized. Natural killer activity (NK) and lymphoproliferation in response to the mitogens concanavaline A (Con A) and lipopolysaccharide (LPS), were studied in peritoneal leukocytes. Both treatments with soybean or green tea plus soybean were highly effective in improving these immune parameters with respect to control groups. Since the immune system is a marker of health and a predictor of longevity, an adequate treatment with isoflavones could be useful in slowing down the effects of the aging process through an improvement in the two relevant immune functions studied.
Artículos en revistas